Matrix Pathobiology and Angiogenesis - Papadimitriou, Evangelia; Mikelis, Constantinos M. (Cham : Springer International Publishing : Imprint: Springer, 2023)
In the vasculature, the extracellular matrix (ECM) is involved in the regulation of angiogenesis, vascular mechanosensing, and blood vessel stability. This book aims to provide the reader with an overview of the various roles of the ECM during angiogenesis and covers its important role for the maintenance of vascular integrity, capillary and arterial morphogenesis, as well as lymphangiogenesis. Furthermore, aspects of regulation of endothelial cell and pericyte functions by the ECM under physiological and pathological conditions are discussed. In addition, the reader will learn more about different approaches to exploit ECM molecules for designing therapeutic approaches or as biomarkers to improve therapeutic decisions. Comprehensive and cutting-edge, Matrix Pathobiology and Angiogenesis is a valuable resource for experienced researchers and early career scientist alike, who are interested in in learning more about this exciting and developing field. The series Biology of Extracellular Matrix is published in collaboration with the American Society for Matrix Biology and the International Society for Matrix Biology.
Chapter 1: Fibronectin Fibrillogenesis during Angiogenesis -- Chapter 2: Functional Interplay Between Fibronectin and Matricellular Proteins in the Control of Endothelial Tubulogenesis -- Chapter 3: Endothelial Cell-Matrix Interactions in Angiogenesis and Vessel Homeostasis: A Focus on Laminins and Their Integrin Receptors -- Chapter 4: Collagens and collagen-degrading enzymes in the regulation of angiogenesis -- Chapter 5: Kruppel-like factor 2 and matrix metalloproteinases in the context of vasculature -- Chapter 6: Extracellular Matrix-Remodeling Enzymes as Targets for Natural Antiangiogenic Compounds -- Chapter 7: Cell - extracellular matrix adhesions in vascular endothelium -- Chapter 8: Hypoxia: a potent regulator of angiogenesis through extracellular matrix remodeling -- Chapter 9: Leading roles of heparan sulfate in angiogenesis and cancer -- Chapter 10: The role of pericytes in tumor angiogenesis -- Chapter 11: Lymphatic Mechanoregulation in Development and Disease.
Keywords: Blood-vessels -- Growth; Cytology; Clinical biochemistry; Angiogenesis; Cell Biology; Medical Biochemistry